Negative Inferential Style, Emotional Clarity, and Life Stress: Integrating Vulnerabilities to Depression in Adolescence - Stange, Jonathan P. (2012)
OBJECTIVE: Negative inferential style and deficits in emotional clarity have been identified as vulnerability factors for depression in adolescence, particularly when individuals experience high levels of life stress. However, previous research has not integrated these characteristics when evaluating vulnerability to depression. METHOD: In the present study, a racially-diverse community sample of 256 early adolescents (ages 12 and 13) completed a baseline visit and a follow-up visit nine months later. Inferential style, emotional clarity, and depressive symptoms were assessed at baseline, and intervening life events and depressive symptoms were assessed at follow-up. RESULTS: Hierarchical linear regressions indicated that there was a significant three-way interaction between adolescents’ weakest-link negative inferential style, emotional clarity, and intervening life stress predicting depressive symptoms at follow-up, controlling for initial depressive symptoms. Adolescents with low emotional clarity and high negative inferential styles experienced the greatest increases in depressive symptoms following life stress. Emotional clarity buffered against the impact of life stress on depressive symptoms among adolescents with negative inferential styles. Similarly, negative inferential styles exacerbated the impact of life stress on depressive symptoms among adolescents with low emotional clarity. CONCLUSIONS: These results provide evidence of the utility of integrating inferential style and emotional clarity as constructs of vulnerability in combination with life stress in the identification of adolescents at risk for depression. They also suggest the enhancement of emotional clarity as a potential intervention technique to protect against the effects of negative inferential styles and life stress on depression in early adolescence.